A systematic approach to exploring college and career readiness program needs within high-poverty urban public schools - Yavuz, Olcay; Parzych, Jennifer; Generali, Margaret (Education and Urban Society, 2019)
This quantitative correlational study was designed to investigate whether the core and enrichment college readiness program needs within high-poverty urban schools significantly varied with respect to grade level and stakeholder perceptions. Statistically significant differences were discovered in parent, student, and faculty perceptions in core and enrichment programs related to high-poverty urban school needs. The findings provide valuable information about how to design student academic and counseling services strategically and effectively to increase college and career readiness for low-income, urban students. Findings also provide effective strategies for school leaders, educators, and counselors regarding urban school college and career readiness program needs so that resources can be intentionally distributed in areas of greatest importance.
Keywords: accountability; change; dept.csp; dept.edl; peer-reviewed; school improvement; school reform; urban education

Racial identity: Choices, context, and consequences - Csizmadia, Annamaria; White, Susan (Biracial families: Crossing boundaries, blending cultures, and challenging racial ideologies, 2019)
Greater public visibility, growing social acceptance, and institutional recognition have opened up the opportunity for many contemporary biracial individuals to choose from a variety of racial identity options. Although macro-level (e.g., legal) barriers have all but disappeared, microlevel challenges (e.g., multiracial microaggressions) still persist for some in the growing biracial population. Thus, it is important to understand how racial identity options are exercised differently within and across particular social contexts, and how these options in turn affect biracial individuals’ development. In this chapter, first we discuss theory and research on racial identity and identification among contemporary biracial people, followed by a brief review of work on the contextual factors that influence racial identity formation in this population. Next, we explore extant research on the association of racial identity to a host of developmental outcomes (e.g., depression, self-esteem, psychological well-being, life satisfaction). In recognition of the heterogeneous nature of the biracial population, we review, where available, research for specific biracial subgroups (e.g., Black-White, Latino-White, and Asian-White). Drawing on relevant theory and empirical findings, we will then make specific recommendations on how to support biracial children’s racial identity formation and social-emotional development and on how to enhance biracial adults’ functioning. Finally, we summarize important gaps in current research and identify needed directions for future research.
Keywords: Academic adjustment; Contextual influences; Developmental diversity; Health behaviors; Psychosocial adjustment; Racial identity; Social context; dept.csp